2018
DOI: 10.4084/mjhid.2018.031
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Endocrine Function in Tunisian Thalassemia Major Patients

Abstract: β-thalassemia major (β–TM) is among the most common hereditary disorders imposing high expenses on health-care system worldwide. The patient’s survival is dependent on lifetime blood transfusion which leads to iron overload and its toxicity in various organs including endocrine glands. This article provides an overview of endocrine disorders in beta-TM patients. This single center investigation enrolled 28 β-TM patients (16 males, 12 females) regularly transfused with packed red cell since early years of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…After that, 433 records were excluded, and 213 records entered full-text assessment for eligibility criteria. Finally, 74 studies included in the meta-analysis ( Figure 1 ) [ 6 7 11 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…After that, 433 records were excluded, and 213 records entered full-text assessment for eligibility criteria. Finally, 74 studies included in the meta-analysis ( Figure 1 ) [ 6 7 11 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study reported a prevalence of 86.8% of their total sample size of transfusion-dependent thalassemics having at least one endocrinopathy, 14 which is close to the 87.4% found in our sample and in keeping with the previously published literature. 15 The most common endocrine complication encountered was low bone mineral density at a prevalence of 72.6% with a statistically significant bias towards the female gender. This was followed by hypogonadism at a prevalence of 44.5% with a statistical significance correlated to patients who underwent a splenectomy.…”
Section: Discussionmentioning
confidence: 98%
“…26 Moreover, excessive iron supplementation in infants and young children have been associated with reduced linear growth. [27][28][29] It is therefore not surprising that a high prevalence of short stature has been reported in HC, affecting over 50% of patients with BTM, 18,23,30,31 and up to 40% of all transfusion-dependent thalassemias (TDT). 32,33 As stated above, growth impairment may originate from endocrine factors such as growth hormone deficiency (GHD) linked to pituitary dysfunction and low IGF-1 levels resulting from liver dysfunction.…”
Section: Pathogenesis Of Growth and Puberty Disorders In Hcmentioning
confidence: 99%
“…A significant proportion of patients with BTM (50%-72%) exhibit reduced IGF-1 levels, 30,34,35 while only 8%-30% 18,35,36 experience impaired growth hormone (GH) secretion (assessed through provocative tests). Notably, decreased IGF-1 levels were also observed in patients with normal GH secretion, possibly linked to liver GH-receptor and/or in post-receptor signaling impairment 34,35 or a decline in liver protidosynthetic activity.…”
Section: Pathogenesis Of Growth and Puberty Disorders In Hcmentioning
confidence: 99%
See 1 more Smart Citation